PENGARUH KOMPETENSI KERJA, KARAKTERISTIK KARYAWAN DAN GAYA KEPEMIMPINAN VISIONER TERHADAP KINERJA PEGAWAI PADA PT. ALAM WISESA PRATAMA - Claudia Meilani Putri Siahaan; Sahat P. Remus Silalahi; Jon Henri Purba; Jeudi Agustina T. P. Sianturi (Universitas Methodist Indonesia, 2023)
This study aims to examine the effect of work competence, employee characteristics and visionary leadership style at PT. alamwisesa pratama. Samples were carried out using the saturated sample method. Data was collected by using questionnaires distributed directly to employees as many as 50 questionnaires. The results of this study indicate that simultaneously work competence, employee characteristics and visionary leadership style have a significant effect on employee performance. Partial test shows that work competence, employee characteristics and visionary leadership style have a positive and significant effect on performance.